EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT DAN NUMBERED HEADS TOGETHER DITINJAU DARI KECERDASAN EMOSIONAL SISWA - Agus Margono; Budiyono Budiyono; Imam Sujadi (Jurnal Ilmiah Guru Caraka Olah Pikir Edukatif, 2017)
The purposes of this study were to determine: (1) which has better learning achievement in mathematics, the application of TGT type cooperative learning,NHT type cooperative learning, or direct learning, (2) which has better learningachievement, the students with high emotional intelligence, medium, or low,(3) which has better learning achievement at each level of high, medium, andlow emotional intelligence on cooperative learning model TGT, NHT, or directlearning, (4) which hasbetter learning achievement on students with high, mediumor low intelligence emotional at each learning of TGT, NHT, and direct learning.This research was a quasi experimental with 3 × 3 factorial design. The studypopulation were seventh grade student of Junior High School State of Yogyakarta. Sampling was done by stratified cluster random sampling with sample of the study were the students of SMPN 1, SMPN 12, and SMPN 14. Each of samples consists of three classes as TGT models class, NHT models class, and control class. The number of total members sample were 303 students. The instrument used to collect the data was mathematics achievement test instruments and students emotional intelligence questionnaire instrument. From the analysis it was concluded that: (1) TGT learning model has better achievement than NHT model and direct learning, NHT learning model has better achievement than direct learning, (2) the students with high emotional intelligence has better achievement than the students with medium and low emotional intelligence, while the students with medium emotional intelligence has better achievement than the students with low emotional intelligence, (3) the students with high emotional intelligence hasthe same achievement on TGT, NHT, or Direct Learning model; the students with medium intelligence, TGT model has better performance than NHT model, NHT model has the same achievement as direct learning model, TGT model has the same achievement as direct learning model; the students with low emotional intelligence hasthe same achievement on learning TGT model, NHT model, and direct learning, (4) the students with high, medium and low emotional intelligence has the same performance on TGT and NHT learning; on Direct Learning, the students with high emotional intelligence has better achievement than students with low emotional intelligence, the students with high emotional intelligence has the same achievement as medium emotional intelligence, the students with medium emotional intelligence has the same achievement as low emotional intelligence